To find a sequence of rigid transformations that maps rectangle ABCD to rectangle A"B"C"D", we first need to identify what transformations are required. Rigid transformations include translations and reflections.
- If rectangle A B C D is reflected over the y-axis, the mapping can be expressed as \( (x, y) \to (-x, y) \).
- Next, if we need to move the new rectangle (after reflection) down by 4 units, this can be expressed as \( (x, y) \to (x, y - 4) \).
The complete transformation sequence that maps ABCD to A"B"C"D" can be expressed as a composition of these transformations:
- Reflect over the y-axis: \( (x, y) \to (-x, y) \)
- Translate down by 4 units: \( (x, y) \to (x, y - 4) \)
In terms of composition, this can be written as:
- First reflect: \( (x, y) \to (-x, y) \)
- Then translate: \( (-x, y) \to (-x, y - 4) \)
Putting these operations together, the sequence of transformations is:
\[ (x, y) \to (-x, y) \to (-x, y - 4) \]
However, in terms of a single transformation:
The composition can be represented as: \[ (x, y) \to (-x, y - 4) \]
Therefore, the answer is: \( (x,y) \to (-x, y - 4) \)
So the final answer is: (x,y)→(−x,y−4).